Environmental Toxic Metals and Metalloids Exposure and Cardiovascular Health: Current Evidence from Oxidative Stress and Inflammatory Biomarkers as Indicators of Subclinical Cardiovascular Effects - Silvia Baldacci; Elisa Bustaffa; Olivia Curzio; Andrea Borghini; Gabriele Donzelli; Chiara Cavigli; Fabrizio Minichilli (Antioxidants, 2026)
Cardiovascular diseases remain the leading cause of global mortality, and environmental toxic metals and metalloids (TMMs) exposure has emerged as an important and potentially modifiable cardiovascular (CV) risk factor. Due to their persistence, bioaccumulation, and widespread distribution, represent a significant public health concern and have been associated with adverse CV outcomes. Mechanistically, TMM-induced cardiotoxicity is primarily mediated through oxidative stress (OS) and inflammatory pathways. Accordingly, related biomarkers, may be considered markers of biological effect and potential pathophysiological mediators associated with TMM exposure. This narrative review summarizes epidemiological evidence linking environmental TMMs exposure with OS and inflammatory biomarkers to CV outcomes. A structured literature search identified 1915 records in PubMed, of which 42 epidemiological studies met the inclusion criteria. The reviewed evidence consistently indicates that environmental and occupational TMMs exposure is associated with significant alterations in biomarkers of lipid peroxidation, antioxidant defense, systemic inflammation, and endothelial dysfunction, all of which reflect early biological CV effects associated with exposure. However, substantial heterogeneity across studies and the predominance of cross-sectional designs limit causal inference and the evaluation of their predictive capacity for future CV events. Future prospective studies integrating mixture-based exposure assessment, standardized biomarker measurements, and multi-omics approaches are needed to clarify whether these biomarkers can serve as markers of biological effect or subclinical CV toxicity and as potential mediators of CV risk, while also assessing their potential contribution to cardiovascular risk stratification in exposed populations.